INTRODUCING DUSSEL: THE PHILOSOPHY OF LIBERATION AND A REALLY SOCIAL PSYCHOLOGY. - Burton, Mark; Osorio, Jorge Mario Flores (PINS-Psychology in Society, 2025)
The work of Argentinian-Mexican philosopher Enrique Dussel is presented in outline, focusing on his intellectual history as a thinker from the global periphery. We explore his reconstruction of the history of modernity and critique of Eurocentrism, his reconstruction of the later Marx, his concepts of analectics and trans-modernity, and his ethical framework. Finally we consider his relevance for psychology in the context of the debate over modernism, indicating some features of a Dusselian, transmodern psychology.